2013
DOI: 10.3906/biy-1212-27
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic diversity in naturally growing 29 Trifolium L. taxa from Bolu Province using RAPD and SSR markers

Abstract: Two molecular marker technologies, RAPD and SSR, were used to determine the genetic diversity of 29 taxa of Trifolium L. collected from Bolu Province. The analysis was carried out using 11 RAPD and 5 SSR markers. A total of 446 and 331 fragments were produced by RAPD and SSR markers, respectively. The amplification products were 300-3500 bp with RAPD and 125-3000 bp with SSR markers. These bands were scored as absence and presence for all taxa. Data obtained were used to estimate genetic similarity using Jacca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…However, molecular studies show that there are still taxonomic problems and some species are not grouped together with other species belonging to the same section [8]. Furthermore it is observed in some studies that the taxa belonging to section Chronosemium are found together with the taxa belonging to other sections (Vesicaria and Lotoidea) [7], unlike the new infrageneric classification proposed by Ellison et al [5].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, molecular studies show that there are still taxonomic problems and some species are not grouped together with other species belonging to the same section [8]. Furthermore it is observed in some studies that the taxa belonging to section Chronosemium are found together with the taxa belonging to other sections (Vesicaria and Lotoidea) [7], unlike the new infrageneric classification proposed by Ellison et al [5].…”
Section: Introductionmentioning
confidence: 95%
“…Besides the members of the genus have great importance for animals, the most of species classification of the species based on the sections or subgenus. While some researchers use the classification proposed by Zohary and Heller [3,6,7], some researchers use the classification proposed by Ellison et al [2,5]. In the classification of Trifolium taxa based on Zohary and Heller [6], the taxa are evaluated into 8 sections as Lotoidea, Paramesus (C.Presl), Mistyllus (C.Presl), Vesicaria, Chronosemium, Trifolium, Trichocephalum Koch, and Involucrarium Hooker.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development and use of molecular marker technologies has also facilitated the subsequent cloning and characterization of disease-, insect-, and pestresistance genes from a variety of plant species including wheat (Hammond-Kosack and Jones, 1997;Meyers et al, 1999). Polymerase chain reaction (PCR)-based assays for plant DNA fingerprinting (Ateş Sönmezoğlu et al, 2012;Göçmen Taşkın et al, 2012;Surgun et al, 2012;György et al, 2013;Uslu et al, 2013), amplified fragment length polymorphism (AFLP), has been developed, which reveals significant levels of DNA polymorphism (Vos et al, 1995). The combination of bulk segregant analysis (Michelmore et al, 1991) and high polymorphic PCR-based markers permit the identification and mapping of useful molecular markers for breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…Polymerase chain reaction (PCR)-based assays for plant DNA fingerprinting (Ateş Sönmezoğlu et al, 2012;Göçmen Taşkın et al, 2012;Surgun et al, 2012;György et al, 2013;Uslu et al, 2013), amplified fragment length polymorphism (AFLP), has been developed, which reveals significant levels of DNA polymorphism . The combination of bulk segregant analysis (Michelmore et al, 1991) and high polymorphic PCR-based markers permit the identification and mapping of useful molecular markers for breeding programs.…”
Section: Introductionmentioning
confidence: 99%